2006
DOI: 10.1111/j.1460-2695.2006.00964.x
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial ratchetting in steels with different cyclic softening/hardening behaviours

Abstract: A B S T R A C TThe cyclic deformation of three structural steels, SS316L stainless steel, 40Cr3MoV bainitic steel and 25CDV4.11 steel, were studied experimentally by uniaxial cyclic straining or stressing tests at room temperature. The cyclic softening/hardening behaviours of the steels were discussed first by cyclic straining tests; and then the effects of cyclic softening/hardening behaviours on the uniaxial ratchetting of the materials were investigated by asymmetrical cyclic stressing tests. It is conclude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 34 publications
4
36
0
Order By: Relevance
“…Non-proportional loading histories induced greater hardening than those of proportional and resulted in slower rates in the ratcheting progress over multiaxial stress cycles [37]. To study the influence of non-proportionality, complex loading paths, and loading steps on ratcheting response of materials, several ratcheting experiments have been conducted [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Hassan et al [5,8,43] investigated the capability of kinematic hardening rules in ratcheting simulation of materials under multiaxial stress cycles and reported that the effect of non-proportionality was yet to be fully addressed.…”
mentioning
confidence: 99%
“…Non-proportional loading histories induced greater hardening than those of proportional and resulted in slower rates in the ratcheting progress over multiaxial stress cycles [37]. To study the influence of non-proportionality, complex loading paths, and loading steps on ratcheting response of materials, several ratcheting experiments have been conducted [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Hassan et al [5,8,43] investigated the capability of kinematic hardening rules in ratcheting simulation of materials under multiaxial stress cycles and reported that the effect of non-proportionality was yet to be fully addressed.…”
mentioning
confidence: 99%
“…[24,25], discussed ratcheting with time independent formulation. The effect of time dependence in ratcheting models is discussed in literature [26,27]. For the present analysis, the constitutive models for Model-1 and Model-2 are discussed in the following sections.…”
Section: Description Of Constitutive Models and Materials Parametersmentioning
confidence: 99%
“…Comparison of ratcheting for steel 316 L in the original condition (1); after prior cyclic strengthening (2): solid lines are experiment[4], dashed lines are calculation.…”
mentioning
confidence: 99%
“…Results are provided in [4] for ratcheting tests at room temperature for steel SS316L. Specimens were tested in tension -compression with a loading rate of 52 MPa/sec with an average cycle stress of 64 MPa and amplitude of 247 MPa (Fig.…”
mentioning
confidence: 99%